Prestasi Akademik Ditinjau dari IQ dan Jalur Masuk Perguruan Tinggi Mahasiswa Psikologi Universitas Negeri Makassar - Astiti Tenriawaru Ahmad; Eva Meizara Puspita Dewi; Basti (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Student academic achievement indicators are known as the Grade Point Average (GPA). The GPA score of a student is a picture of a student's academic performance while studying at Higher Education (PT). Students will get a grade point index every semester so they will know how much score they get for each subject that has been printed on the Study Plan Card (KRS). Obtaining a GPA which is a description of student academic achievement is of course influenced by many factors both internal and external to students. One of the internal factors that play a role in the academic process is the intelligence factor. Adequate intelligence abilities make it easier for students to understand lecture material. Basically, students' cognitive abilities are not only seen through IQ, academic performance before entering higher education is also a consideration for students to be accepted at a tertiary institution. Because of this, there are various pathways into Higher Education that students can take by considering the academic grades obtained in high school. Students who have academic and non-acadebjwhmic achievements and take the SNMPTN route. For prospective students who do not excel in high school, they can take the SBMPTN route. Furthermore, some students who do not pass the SBMPTN will usually take the independent route to enter PT. In this regard, this study aims to determine differences in academic achievement and potential in terms of university entry pathways. This research captures the potential of 427 new students from the Faculty of Psychology, Makassar State University (UNM). The instruments used are questionnaires and IQ tests. This type of research is a quantitative research with logistic regression analysis using SPSS statistics and its implications are used as a basis for seeing student potential. The results of the study show two research results, namely 1) There is a relationship between IQ and learning achievement in Class 2021 Students of the Faculty of Psychology UNM, 2) There is a significant difference in the learning achievement of Class 2021 Students of the Faculty of Psychology UNM in terms of university entry pathways.